2022
DOI: 10.1136/bmjopen-2021-059213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of endovenous microwave ablation versus laser ablation for great saphenous vein varicosis: study protocol for a multicentre, randomised controlled non-inferiority trial

Abstract: IntroductionEndovenous microwave ablation (EMA) is a relatively novel thermal ablation treatment for great saphenous vein (GSV) varicosis, and its efficacy and safety are rarely reported. This study aims to explore whether EMA can be comparable to endovenous laser ablation (EVLA), which is a widely used thermal ablation treatment in clinical practice.Methods and analysisThis is a multicentre, randomised controlled non-inferiority trial to compare the efficacy and safety of EMA and EVLA in patients with GSV var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In a previous study compared between EMA and ELVA and they stated that EMA resulted in lower ecchymosis complications, but higher skin burns compared to EVLA [10] . Mao et al, [24] conducted a retrospective study comparing between EVLA and EMA and their results showed that EMA resulted in lower ecchymosis incidence, but higher skin burn than EVLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study compared between EMA and ELVA and they stated that EMA resulted in lower ecchymosis complications, but higher skin burns compared to EVLA [10] . Mao et al, [24] conducted a retrospective study comparing between EVLA and EMA and their results showed that EMA resulted in lower ecchymosis incidence, but higher skin burn than EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…The other techniques such as microwaves has considered to be safe with good clinical outcomes in treatment of VVs. EMA is a relatively new technique for thermal ablation therapy that produces thermal energy in a manner differ from EVLA [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Endovenous microwave ablation (EMWA) is a relatively new catheter-based EVTA system. Although reasonable ablation rates have been reported 95-100% at 12 months [4][5][6] and even 98% at 5 years, 7 the power parameters currently used vary widely, from 20 W-65 W, [4][5][6][7] with a future multicentre randomised controlled study planning to use a power of 65 W. 8 Doctors working with EVLA report the energy used for ablation as the Linear Endovenous Energy Density (LEED) 9 the energy used per cm of vein treated. However, the wide variation of power, pullback and intermittent ablation and rest cycle combinations reported by those using EMWA have not included the LEED, 4-8, making comparing devices and reported outcomes challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The UMA for varicose veins presents as a promising alternative to conventional surgery, mainly due to its minimally invasive approach which significantly reduces the risk of postoperative wound infections. Additionally, UMA offers the advantages of shorter procedure times and reduced hospital stays, enhancing patient recovery and comfort 6,7 …”
Section: Introductionmentioning
confidence: 99%